Muscle-Specific Micro-Ribonucleic Acids miR-1-3p, miR-133a-3p, and miR-133b Reflect Muscle Regeneration After Single-Dose Zoledronic Acid Following Rotator Cuff Repair in a Rodent Chronic Defect Model. Issue 12 (October 2022) - Schanda, Jakob E.; Heher, Philipp; Weigl, Moritz; Drechsler, Susanne; Schädl, Barbara; Prueller, Johanna; Kocijan, Roland; Heuberer, Philipp R.; Hackl, Matthias; Muschitz, Christian; Grillari, Johannes; Redl, Heinz; et al.
Background: Zoledronic acid improves bone microarchitecture and biomechanical properties after chronic rotator cuff repair (RCR) in rats. Besides the positive effects of zoledronic acid on bone mineral density and bone microarchitecture, bisphosphonates have positive effects on skeletal muscle function. Purposes/Hypothesis: The purposes of this study were to (1) longitudinally evaluate circulating bone- and muscle-specific serum micro-ribonucleic acids (miRNAs) and (2) investigate supraspinatus muscle tissue after tenotomy and delayed RCR in a rat model. It was hypothesized that zoledronic acid would improve muscle regeneration after chronic RCR in rats. Study design: Controlled laboratory study. Methods: A total of 34 male Sprague-Dawley rats underwent unilateral (left) supraspinatus tenotomy (time point 1) with delayed transosseous RCR after 3 weeks (time point 2). All rats were sacrificed 8 weeks after RCR (time point 3). Animals were randomly assigned to 2 groups. One day after RCR, the control group was given 1 mL of subcutaneous saline solution, and the intervention group was treated with a subcutaneous single-dose of 100 µg/kg body weight of zoledronic acid. All 34 study animals underwent miRNA analysis at all 3 time points. In 4 animals of each group, histological analyses as well as gene expression analyses were conducted. Results: Circulating miRNAs showed significantly different expressions between both study groups. In the control group, a significant downregulation was observed for muscle-specific miR-1-3p ( P = .004), miR-133a-3p ( P < .001), and miR-133b ( P < .001). Histological analyses showed significantly higher rates of regenerating myofibers on the operated side (left) of both study groups compared with the nonoperated side (right; P = .002). On the nonoperated side, significantly higher rates of regenerating myofibers were observed in the intervention group compared with the control group ( P = .031). The myofiber cross-sectional area revealed significantly smaller myofibers on both sides within the intervention group compared with both sides of the control group ( P < .001). Within the intervention group, significantly higher expression levels of muscle development/regeneration marker genes embryonal Myosin heavy chain ( P = .017) and neonatal Myosin heavy chain ( P = .016) were observed on the nonoperated side compared with the operated side. Conclusion: An adjuvant single-dose of zoledronic acid after RCR in a chronic defect model in rats led to significant differences in bone- and muscle-specific miRNA levels. Therefore, miR-1-3p, miR-133a-3p, and miR-133b might be used as biomarkers for muscle regeneration after RCR. Clinical Relevance: Adjuvant treatment with zoledronic acid may improve muscle regeneration after chronic RCR in humans, thus counteracting fatty muscle infiltration and atrophy.